Characterization of chaperone-like activity of small heat shock protein (sHSP) isolated from Indonesian Traditional Food (Tempoyak ) Lactobacillus plantarum U10 (Microbiology Indonesia, 2014)
The characterization of small heat shock protein (sHSP) from tempoyak-originated Lactobacillus plantarum was investigated. The heat adaptive response proteins were ranging from 18 kDa to 51 kDa. Interestingly, the Intercellular Protein (IP) fraction of heat shocked-L.plantarum U10 exhibited chaperone like activity by the ability to prevent loss of proteinase K activity from denaturation. Furthermore, The sHSP gene that related to the predicted sHSP ±18 kDa protein were successfully identified by PCR method and this gene has 423 bp size. The sHSP gene has 140 amino acids (with unique motive at C-terminus T-L-P-K amino acid sequence) and has closely 100% identity with those L.plantarum isolated from food or non-food environment. Moreover, the gene encoding sHSP ±18 kDa protein was indeed up-regulated after L.plantarum U10 treated by heat shocking as proven by Reverse Transcriptase-PCR. This result suggested that sHSP ±18 kDa in our study may confers a survival advantage on Lactobacillus plantarum and capable of protecting the cell against under temperature stress.